Learning qualitative methodology in doctoral management research - Said, Mohd Fuaad; Adham, Khairul Akmaliah; Sarkam, Saida Farhanah (2015)
Literature suggests that the learning of qualitative methodology is a craft that requires a close interaction between a student and a teacher. However, thus far, there is a lack of discussion on how qualitative methodology is learned. The lack of knowledge about the use of qualitative methodology could have serious consequences on the practices of management in organisations as well as for future studies. These include possible rejection and misuse of the methodology amongst researchers. To address this gap, the objective of the paper is to suggest a framework on doctoral learning process of qualitative methodology. To achieve this objective, we review literature on learning qualitative methodology in management. Based on this review, we introduce the concept of doctoral research, covering the topics of doctoral research process and doctoral program in management. Next, we discuss the concept of qualitative research in management by presenting the definition of qualitative research and the use of qualitative research. We later describe the required knowledge and skills in conducting qualitative research in management and the methods of learning them. Finally, we propose a framework that i) relates doctoral research process and the learning methods; ii) relates learning methods to the types of knowledge and skills required to conduct qualitative methodology, and iii) points out the importance of having the right interval values in helping students achieve completion of their doctoral program.